PENGARUH INSENTIF DAN BUDAYA SEKOLAH TERHADAP KINERJA GURU PADA SDN 013 BALIKPAPAN SELATAN - Sri Guwarah; Nugroho Mardi Wibowo; C. Sri Hartati (Jurnal Manajerial Bisnis, 2018)
This study aims to determine the description of incentives, school culture and teacher performance at SDN 013 South Balikpapan and to know the incentives and school culture simultaneously and partially influence the performance of teachers in SDN 013 South Balikpapan and to know among the incentives and school culture that has a dominant effect on Performance of teachers at SDN 013 Balikpapan Selatan. This research uses quantitative approach and explanatory research type. The population in this research is all teachers of SDN 013 Balikpapan Selatan. The sample of this study amounted to 30 teachers. The sampling technique uses a saturated sample. Methods of data collection using questionnaires and documentation. The results of this study indicate that the incentive teachers SDN 013 South Balikpapan in good category, school culture SDN 013 Southern Balikpapan is also in good category. There is a simultaneous influence between school incentives and culture on teacher performance SDN 013 Balikpapan Selatan. There is partial influence between school incentive and culture on teacher performance SDN 013 Balikpapan Selatan. Keywords: incentives, school culture, teacher performance